Probiotics: Outweighing pros and cons - Sarmistha Dey; Sonal P Vahanwala; Sandeep S Pagare (Wolters Kluwer Medknow Publications, 2011)
In recent few years, our markets had a boom of probiotic drinks and probiotic ice creams. The media and various endorsements can often mislead the consumers. We, as healthcare providers also shoulder a duty to decide and outweigh the pros and cons of this newly developed concept.